EFEKTIVITAS DOSIS DAN WAKTU APLIKASI Trichoderma virens TERHADAP SERANGAN Sclerotium rolfsii PADA KEDELAI - Tjut Chamzurni; Rina Sriwati; Rahel Rahel (Jurnal Floratek, 2011)
This study was aimed at obtaining an effective dose and application timing of Trichoderma in controlling wilt disease caused by Sclerotium on soybean. This study used a factorial complete ramdomized design with 8 combination of treatments and 4 replications. There were two factors studied, dose and timing of Trichoderma. Four level doses factor were studied, i.e. 75, 150, 225, and 300 g.polybag-1, while timing of application consisted of 2 levels, 7 days before planting and at the planting time. The observed variables were germination rate, incubation period, length of lesion formed on the base of the stem, and dry weight of seeds per plant. Data of variables observed was analized by analysis of variance and followed by least significance different test at level 5%.  The results showed that dose of Trichoderma gave a significant effect on seed germination rate, incubation period, length of lesion and dry weight of seed per plant. Dose of Trichoderma 300 g.polibag-1 was the best and gave  germination rate of seed up to 84,38%, incubation period 8 days, length of lesion 1,35 cm and dry weight of seed 24,13 g. The timing of application gave a significant effect only on dry weight of seed per plant.  The best timing of application was found at 7days before planting and no interaction between doses and time of application of Trichoderma.